Chicken soup for little souls : the Goodness Gorillas - McCourt, Lisa.; Porter, Pat Grant; Canfield, Jack, 1944-; Porter, Pat Grant (Deerfield Beach, Fla. : Health Communications, 1997)
Jessica and her classmates form a club whose mission is to perform acts of kindness, even for the meanest boy in the class.
"Based on the ... best-selling series Chicken soup for the soul by Jack Canfield and Mark Victor Hansen."
Keywords: Kindness -- Fiction; Clubs -- Fiction; Conduct of life -- Fiction; Schools -- Fiction